Vale S.A.: Cobalt Streaming - Freitas, Flavia D'Albergaria; Campani, Carlos Heitor; Moszkowicz, Viktor Nigri; Roquete, Raphael Moses; Maranho, Flavia Schwartz (SciELO journals, 2021)
ABSTRACT The case “Vale S.A. — Cobalt Streaming” describes a transaction that has taken place at Vale, a Brazilian mining company, and one of the most important in its segment. The transaction was developed to de-risk an important project for an expansion of a mine in the province of Newfoundland & Labrador in Canada. By streaming the cobalt production, Vale was able to get a competitive internal rate of return for the project compared to the lower level of risk the project would then offer. The case detailed the negotiation since the beginning until the company faced the challenge of choosing from the final proposals. The case allows the discussion of important aspects regarding project valuation: risk mitigation through the streaming negotiation, several different types of risk influencing the main issue of the case, decisions about the assumptions used, discussion about debt/equity characteristics on the overall project from Vale’s perspectives, and the evaluation of a project with non-conventional cash flow, given a substantial upfront revenue due to the streaming contract. So, the case is recommended for the disciplines of Financial Management, Project Valuation, or Risk Analysis in post-graduate courses of Business Administration and Finance.